Implementasi Prinsip Rahasia Bank Terhadap Pengungkapan Tindak Pidana Pencucian Uang dan Pendanaan Terorisme - Nancy Andriany Napitupulu; Suhaidi; Bismar Nasution; Hamdan (Idarotuna : Journal of Administrative Science, 2022)
Nowadays, criminals usually don't put their illegal money straight into the open air. They will disguise the illegal money by placing them in the banking system. Criminal organizations need to keep their illegal money undetected by the police. As a financial institutions, banks can be used as facilities for Money Laundering. There are also bank secrecy regulations, which require every bank as a Financial Institution to be confidential in providing information about their customers and their deposits. Several countries in the world see bank secrecy as a strict regulation. Indonesia is one of the countries that see bank secrecy as a relative regulation, which means that it can be disbursed for the public interest, such as for state tax proceedings, civil courts and private courts. Therefore, this relative regulation may create some difficulties for law enforcement to enforce.